193k views
0 votes
Solve for g:2g - h= 5f(2.5+h)fg=1f(5+h)/2(5f+h) / 2MORZoom inO0nouloUS 11:36

Solve for g:2g - h= 5f(2.5+h)fg=1f(5+h)/2(5f+h) / 2MORZoom inO0nouloUS 11:36-example-1

1 Answer

0 votes

Eliminate the denominator by multiplying both sides of the equation by f.


2g-h=5f

Add h to both sides of the equation.


2g=5f+h

Divide both sides of the equation by 2.


g=(5f+h)/(2)

Therefore, the correct answer is the rightmost option.

Solve for g:2g - h= 5f(2.5+h)fg=1f(5+h)/2(5f+h) / 2MORZoom inO0nouloUS 11:36-example-1
User Vivek Mishra
by
5.6k points